Busverkehrsdienstleistungen im Ausschreibungswettbewerb. - Wanner, Karen; Zietz, Axel (Deutscher Verkehrs-Verl., 2008)
Seit zehn Jahren werden im Rhein-Main-Verkehrsverbund (RMV), im Münchner Verkehrs- und Tarifverbund (MVV) und im Hamburger Verkehrsverbund (HVV) Aufträge über Ausschreibungen vergeben. Wie entwickelt sich die Angebotsqualität im Ausschreibungswettbewerb? Wie entwickelt sich die Qualität bei ausgeschriebenen Verkehren im Vergleich zu Bereichen, in denen nicht ausgeschrieben wird? Treibt die Vorgabe hoher Qualitätsstandards die Preise in die Höhe? Was passiert, wenn keine anspruchsvollen Qualitätsstandards vorgegeben werden? Diesen und anderen Fragen ist die Strategie- und Managementberatung KCW GmbH im Auftrag der Verkehrsverbünde RMV, MVV und HVV im Rahmen der Studie "Der Busverkehr im Wettbewerb" nachgegangen. difu

On behalf of the public transport agencies RMV, MW and HW KCW GmbH has analysed all tender actions that have been completed in the three agencies until June 2006. The main research topic was to find out whether the tendering procedure in its present structure would raise the efficiency of short-distance public transport. In fact, the results of the analysis prove that the transport agencies demanding high quality standards as minimum requirement for their vehicles (RMV and MVV) were able to improve their vehicle quality verifiably. But if the minimal quality requirements lie below the quality level of the previous public transport operator, the quality level might possibly decrease. The data related to quality issues permit the conclusion that quality will go on improving. Nevertheless, in order to provide substantial quality assurance it is recommended to set up and administer regularly a database which allows pursuing the development of all relevant quality criteria. In this regard the public transport agencies Section 0 guidelines play a great role. The study did not approve the widely spread assumption that there is a correlation between high quality standards and an accordingly higher tender price. difu
Keywords: Verkehr; Bus; Busverkehr; Ausschreibung; Vergabe; Verkehrsverbund; Verkehrsunternehmen; Fuhrpark; Verkehrsdienstleistung; Qualitätsstandard; Evaluation